2013
DOI: 10.1590/s1983-40632013000200007
|View full text |Cite
|
Sign up to set email alerts
|

Divergência genética de populações de Piper hispidinervum C. DC. com base em caracteres morfoagronômicos

Abstract: Com o intuito de gerar informações para o programa de melhoramento de pimenta longa (Piper hispidinervum), no Estado do Acre, avaliou-se a divergência genética entre quinze populações coletadas em diferentes regiões do Estado. Foram avaliados os seguintes caracteres morfoagronômicos: largura e comprimento da folha, comprimento e diâmetro do pecíolo, volume de copa, rendimento de óleo essencial e teor de safrol (componente majoritário deste óleo essencial). Foram aplicadas análises de agrupamento, pelos métodos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The formation of coincident groups, through the use of complementary methods of multivariate analysis, is also described in pepper (Negreiros & Miqueloni, 2013), passion fruit (Paiva et al, 2014), tomato (Luz et al, 2016;Amaral Júnior et al, 2017;Maciel et al, 2018b), which shows consistency of similarity results in the groups composition. The results obtained in the present study corroborate those found by these authors.…”
Section: Resultsmentioning
confidence: 97%
“…The formation of coincident groups, through the use of complementary methods of multivariate analysis, is also described in pepper (Negreiros & Miqueloni, 2013), passion fruit (Paiva et al, 2014), tomato (Luz et al, 2016;Amaral Júnior et al, 2017;Maciel et al, 2018b), which shows consistency of similarity results in the groups composition. The results obtained in the present study corroborate those found by these authors.…”
Section: Resultsmentioning
confidence: 97%
“…The variability of essential oil yield of long pepper populations (Table 1) is high, which indicates the possibility of genetic gains, as noted by Negreiros and Miqueloni (2013a) for long pepper. On the other hand, safrole content shows a higher degree of homogeneity.…”
Section: Discussionmentioning
confidence: 93%